Boosting the solar conversion efficiency of MoSe2/PtX2 (X = O, S) vdW heterostructure by strain and electric field engineering - Robin Yee Hui, Chang; Hoe Yeoh, Keat; Junke, Jiang; Yen Khong, Heng; Mohd Muzamir, Mahat; Soo See, Chai; Fui Kiew, Liew; Moi Hua, Tuh (IOP Publishing Ltd, 2022)
Vertically stacking two-dimensional materials via weak van der Waals (vdW) forces is an effective strategy for modulating optoelectronic performance of materials. To accelerate more novel MoSe2-based heterostructure design, the interlayer coupling effect in MoSe2/PtX2 (X = O, S) heterostructure has been systematically studied, from the atomic structure to the electronic and optical properties, on the basis of first-principles calculations and BSE model with scissor inclusion. Density functional theory (DFT) calculations unveil a type-II indirect bandgap measuring between 0.85 and 0.91 eV at HSE06 level, with Bader and charge density difference analyses suggesting occurrence of charge redistributions at the interface and electrons diffusion from MoSe2 to PtX2 layers, driven by large band offsets. The thermodynamic and thermal stabilities of the heterostructures are demonstrated by the negative binding energy and AIMD simulation. The heterostructure interface is influenced by the weak vdW coupling with an equilibrium interlayer distance of 3.01 to 3.08 Å and binding energy of −5.5 to −11.2 meV Å−2, indicating an exothermic process and steady adhesion at the interface. Reasonable lattice mismatch that ranges from 1.5 to 4.7% between the vdW heterostructure and separate monolayers suggests good structure compatibility. The optical performance of the heterostructure was examined using the real and imaginary components of dielectric function, where enhanced light absorption of 104–105 cm−1 and prominent peaks are observed encompassing the infrared to ultraviolet domains. Record high spectroscopic limited maximum efficiency (SLME) of ∼33% was also predicted. The absorption strength of MoSe2/PtO2 and MoSe2/PtS2 enhances with increasing negative external electric field (Eext) and compressive strain, individually, inferring their optical properties modulation by Eext and biaxial strain. Both heterostructures present high carrier mobility up to 1322.98 cm2 V−1 s−1 in zigzag direction.